DO beta: a new beta chain gene in HLA-D with a distinct regulation of expression. - Tonnelle, C (1985)
The HLA-D region of the human major histocompatibility complex encodes the genes for the alpha and beta chains of the DP, DQ and DR class II antigens. A cDNA clone encoding a new class II beta chain (designated DO) was isolated from a library constructed from mRNA of a mutant B-cell line having a single HLA haplotype. Complete cDNA clones encoding the four isotypic beta chains of the DR1, DQw1, DPw2 and putative DO antigens were sequenced. The DO beta gene was mapped in the D region by hybridization with DNA of HLA-deletion mutants. DO beta mRNA expression is low in B-cell lines but remains in mutant lines which have lost expression of other class II genes. Unlike other class II genes DO beta is not induced by gamma-interferon in fibroblast lines. The DO beta gene is distinct from the DP beta, DQ beta and DR beta genes in its pattern of nucleotide divergence. The independent evolution and expression of DO beta suggest that it may be part of a functionally distinct class II molecule.